DESIGNING E-LEARNING MODEL TO LEARN ABOUT TRANSPORTATION MANAGEMENT SYSTEM TO SUPPORT SUPPLY CHAIN MANAGEMENT WITH SIMULATION PROBLEMS - Wiyono, Didiek Sri; Pribadi, Sidigdoyo; Permana, Ryan (J@ti Undip : Jurnal Teknik Industri, 2011)
Focus of this research is designing Transportation Management System (TMS) as e-learning media for logistic education. E-learning is the use of Internet technologies to enhance knowledge and performance. E-learning technologies offer learners control over content, learning sequence, pace of learning, time, and often media, allowing them to tailor their experiences to meet their personal learning objectives. E-learning appears to be at least as effective as classical lectures. Students do not see e-learning as replacing classical training but as a complement to it. TMS are one of many system that will be completed the supply chain. To support interoperable machine-to-machine interaction over a network we can use a web service. By using web service, TMS software can communicated with Supply Chain Management (SCM) software and completed the supply chain. In previous research about logistic problems, still limited to the modul design of SCM application without TMS support. We created this e-learning media by using PHP, SOAP, SQL and HTTP connection protocol. The result of the research is web-based e-learning application to learn about transportation with simulation problems to complete the purpose of supply chain on logistics.Key Words: Transportation Management System, Supply Chain Management, Logistic, e-learning media, Web service.Â Fokus dari penelitian ini adalah untuk mendesain sebuah e-learning media mengenai Transportation Management System (TMS) sebagai media pembelajaran untuk mempelajari masalah logistik. E-learning adalah penggunaan teknologi internet untuk meningkatkan pengetahuan dan kinerja. E-learning menawarkan kontrol atas konten, urutan pembelajaran, kecepatan pembelajar, waktu pembelajaran, dan media yang digunakan, untuk memenuhi tujuan dari pembelajaran. Dibandingkan dengan metode pengajaran klasik, e-learning memiliki nilai keefektifan yang sama besar dengan metode pengajaran klasik. E-learning bukan merupakan pengganti dari metode pengajaran klasik melainkan merupakan pelengkap dari metode pengajaran klasik. TMS merupakan satu dari beberapa system yang ada dalam kajian rantai pasok. Dengan menggunakan teknologi web service maka sebuah system dapat berkomunikasi dengan sistem yang lain dalam sebuah jaringan. Dengan menggunakan teknologi web service, TMS dapat berkomunikasi dengan software Supply Chain Management (SCM) untuk melengkapi rantai pasok. Dalam penelitian yang sebelumnya pernah dilakukan hanya terbatas pada pembuatan aplikasi SCM tanpa adanya dukungan dari TMS. Pembuatan e-learning untuk TMS ini adalah dengan menggunakan PHP, SOAP, SQL dan HTTP connection protocol. Hasil dari penelitian ini adalah sebuah e-learning berbasis web untuk mempelajari masalah transportasi dengan menggunakan masalah simulasi untuk melengkapi rantai pasok dalam logistik.Kata kunci: System manajemen transportasi, Supply Chain Management, Logistik, media e-learning, Web service.